Obesidade: o papel das melanocortinas na regulação da homeostasia energética - Rodrigues, Adriana (2011)
Obesity is one of the greatest public health problems of the 21st century, with major consequences in diabetes, cardiovascular diseases and cancer. It is well known that the melanocortin system is an important regulator of body energy homeostasis1. In fact, the role of the melanocortin system in the regulation of energy balance at the central nervous system has been extensively studied, although melanocortins are also involved in other biological processes such as pigmentation or steroidogenesis2-3. In addition, it has also been demonstrated that melanocortins act in a variety of peripheral tissues, including the adipose tissue. The study of peripheral melanocortin effects has been increased and challenges the MCRs as promising targets for the pharmacological treatment of obesity. The role of melanocortins on energy homeostasis is reviewed in this manuscript which describes up to date scientific data.